Qanuqtuurniq—finding the balance: an IPY television series using community engagement - Catherine L. Carry; Kath Clarida; Denise Rideout; Dianne Kinnon; Rhonda M. Johnson (Polar Research, 2011)
The three-part television broadcast Qanuqtuurniq—finding the balance was an International Polar Year communications and outreach project concerning Inuit health and wellness. The goal of this project was to engage the Inuit public and others in “real-time” dialogue about health and wellness issues and health research, and to deliver key messages. It was aired live in the Inuit language (with English captions/sub-titles) from Iqaluit, Nunavut, Canada, in May 2009 and simultaneously webcast. Qanuqtuurniq—finding the balance used an Inuit communications model for remote communities that was developed in the Arctic in 1994 by the Inuit Broadcasting Corporation/Inuit Communications. In Qanuqtuurniq—finding the balance more than 250 people were engaged through the use of a diverse range of methods, including content working groups, stakeholder input, music recordings, pre-recorded community programme videos, live and public screening of the broadcasts, live panels, live audiences, public phone-ins, Skype video-conferencing and real-time online chat, focus groups and e-mail. This article examines the project in light of the principles of “community engagement”, demonstrating that Qanuqtuurniq—finding the balance exemplifies community engagement in a number of significant ways, including heavily involving community members in the selection of the health theme content of the televised programmes and through the formation of focus groups. Based on challenges encountered during the Qanuqtuurniq—finding the balance project, the article offers recommendations for future projects.